Combating Software Piracy in Public Clouds. - Wang, Chia-Wei; Cho, Michael Cheng Yi; Wang, Chi-Wei; Shieh, Shiuhpyng Winston (Computer (00189162), 2015)
CodeMist is an innovative security framework that leverages both passive and active approaches to prevent piracy of cloud-based rental software.